The future of inward and outward investment in Russia - Erokhin, Vasilii (Henry Stewart Talks, 2014)
Foreign investment in the world, Foreign investment in economies in transition, particularly the CIS, Inward and outward investment in Russia, Expected trends of inward and outward investment in Russia